Модернізовані інструменти девелоперського управління будівництвом - Тугай, О. А.; Поколенко, В. О.; Рижакова, Г. М.; Приходько, Д. О.; Лагутіна, З. В.; Стеценко, С. П. (Ways to Improve Construction Efficiency, 2012)
For the first time, to display the organization’s processes contract construction, real estate development scheme implemented by management, proposed a fundamentally new type of resource calendar model, which combines features of the traditional resource-calendar network models with semantic level of confidence in the developer’s compliance with the planned project characteristics and policy requirements of the customer during construction works. Introduce a new model system for the selection of options criterial models of organization development. Accuracy of selection of alternatives provided by the formation of confidence and resource profile of the construction project, which determines the comparative advantage of each alternative relative to another.